Evaluation of Drip Lateral Spacing on Yield and Economic Return of Onion (allium cepa l.) at Awash Melkassa, Ethiopia (American Journal of Agricultural Science, Engineering, and Technology, 2023)
Water availability is becoming a critical issue in Ethiopia in semi-arid climate mainly in Rift Valley areas. Field experiment was carried out during the dry cropping season of 2019/2020 to evaluate the performance of drip lateral spacing on onion yield and its net return with two adjustments of drip lateral spacing at full irrigation application viz., lateral placed in every row and between two rows. The performance of drip lateral spacing system was evaluated on the basis of parameters like emitter flow rate (q), emission uniformity (EU), emitter flow rate (qvar), coefficient of variation (CV), uniformity coefficient (CU). The mean values of upper, middle, and lower lateral spacing showed non- significant (P ≥ 0.05) difference in emission uniformity of drip lateral spacing. An average emitter uniformity parameter value was 93.66%, 96.28%, 12.05 %, 1.68 % for emission uniformity, uniformity coefficient, emitter flow variation and coefficient of variation respectively. The designed drip lateral spacing was operated excellently as all values of emitter uniformity parameter were in the recommended range in each case. The average basic infiltration rate was found to be 18 mm/hr. From the result, onion yield and yield parameters was affected by the effects of drip lateral spacing. Maximum onion bulb yield of 41.44t ha-1 and 25.83t ha-1 were obtained from lateral spacing in every row and between two rows respectively. Total bulb yield was reduced by 37.65% when drip lateral between two rows was used. But the cost of drip lateral between two onion plant rows was 26.14% less than drip lateral in every onion plant rows. Therefore, onion could be irrigated by drip lateral spacing in every row to get better onion bulb yield.